Impact Of Hrm Practices Toward Turnover Intention Among Academicians Of Public Universities Of Sindh, Pakistan: The Roles Of Work Engagement And Organizational Politics - Lata (2020)
Success and progress of the universities is contingent on the competent and engaged academicians. But now days, turnover intention among the academicians has become a significant problem that needs to be addressed and solved. Therefore, the present study aims to investigate the turnover intention among academicians working in public universities of Sindh, Pakistan. Social Exchange Theory (SET) and Conservation of Resource (COR) Theory underlie the model framework in this study.